Cerai Gugat Perspektif Hukum Islam dan Hukum Positif: Analisis Faktor Penyebab Tingginya Angka Cerai Gugat di Pengadilan Agama Sumedang - Rusdi Zam Zam Jauhari; Istiqomah; Habib Al Fadli; Muksin Najarudin Aris; Mohammad Husni Mubarok (Penerbit Lestari Sakha Pustaka, 2026)
Contested divorce (cerai gugat) is a dominant phenomenon in divorce cases at Religious Courts in Indonesia, including the Sumedang Religious Court. This study aims to analyze the concept of contested divorce from the perspectives of Islamic law and Indonesian positive law, and to identify the dominant factors causing the high rate of contested divorce at the Sumedang Religious Court. The research employs a normative-empirical method with a qualitative approach through interviews, observation, and documentation studies. The findings reveal that contested divorce in Islamic law corresponds to the concept of khulu' based on Al-Qur'an Surah Al-Baqarah verse 229, while positive law regulates it through Article 132 of the Compilation of Islamic Law, requiring divorce to be conducted before the Religious Court. The dominant factors include: economic problems, continuous disputes and quarrels, husband's irresponsibility, domestic violence and infidelity, increasing legal awareness and women's independence, and socio-cultural factors such as arranged marriages and lack of spiritual readiness. Mediation efforts at the Sumedang Religious Court have not been effective due to low mediator professionalism and the strong determination of parties to divorce. This study recommends improving mediator quality, strengthening partnerships with BP4, optimizing premarital education, and consistently implementing divorce certificate withholding instruments to guarantee women's rights post-divorce.